THE EFFECT OF SOCIAL INTERACTION ON NEGATIVE VOCABULARY ACQUISITION IN 6-YEAR-OLD CHILDREN: PENGARUH INTERAKSI SOSIAL TERHADAP PEMEROLEHAN KOSAKATA NEGATIF PADA ANAK USIA 6 TAHUN - Dewi Wulandari (Program Studi Pendidikan Bahasa Indonesia, Institut Pendidikan Nusantara Global, 2024)
This study aims to describe how social interaction affects the acquisition of negative vocabulary in 6-year-old children. This research was conducted using descriptive qualitative method. The subject in this study is a 6-year-old boy. The data in the study are negative vocabulary utterances produced by 6-year-old children. The data collection technique applied in this research is direct observation through interviews. The results show that children who communicate less with parents and interact more with the outside environment tend to use more negative vocabulary. Environmental factors, such as home, school, and playground, play an important role in this process. Therefore, it is important for parents and educators to create a conducive environment and provide positive social stimulus to support children's healthy language development.